Development of a prototype of mini robot vacuum cleaner - Abdullah Hanapi, Ahmad Zalikh Iqmal (2024)
A recent study by Hospitality GEM highlighted unclean tables as the fourth most common grievance among diners. Customers typically avoid visibly dirty tables, but they might unknowingly choose seemingly clean yet still dirty ones. In Malaysia, several restaurants were recently shut down due to rat and cockroach infestations, and a viral video exposed maggots in fried chicken at another establishment. While online reviews help gauge cleanliness, the most trustworthy ratings are the grades displayed in restaurants. Dirty tables, leftover food and a shortage of cleaners contribute to uncleanliness, but hiring more workers is often financially challenging for restaurants. Therefore, there is a need to develop a manpower-free solution, such as portable robot vacuum cleaner, which can assist restaurants in maintaining cleanliness. This innovative project aims to benefit various restaurants and simplify table cleaning for workers by using advanced technology for automated cleaning.